Chapter Assessing the predictive capability of Invalsi tests on high school final mark - Bacci, Silvia (Proceedings e report, 2023)
Educational achievement can be considered a multifaceted issue, which comprises different domains of learning. In Italy, on one hand the INVALSI tests administered to students through the schooling years aim to measure the ability of students in numeracy, literacy and English reading and listening competencies, separately. On the other hand, the high school final mark may be considered an overall performance outcome, formed by the combination of several marks in different subjects. Finally, at university academic achievement may be represented by the number of credits earned during the first year of enrolment, usually considered a good predictor of successful academic performances. The aim of the present work is to understand if the INVALSI scores, the high school final mark and the number of credits earned in the first academic year are associated. More specifically, our objective is twofold: first, we intend to verify if and how the INVALSI scores are associated with students' high school final mark; second, we aim to check if the INVALSI scores and / or the high school final mark are predictive of students' career in terms of credits earned in the first year. We will interpret our results concentrating our attention on eventual differences depending on type of school, university, field of study, student's geographical area of residence. We use the MOBYSU.it database, selecting nearly 200.000 students who obtained their high school diploma in Italy in 2019 and enrolled in an Italian university in academic year 2019/2020. For the first objective, we estimate a multilevel ordered logit models, with students nested within high schools; as for the second objective, we estimate a cross-classified multilevel models, with students nested within high schools and athenaeums. We interpret our results in the light of assessing eventual divergences in students' performances during the transition from high school to university.